Outcomes of a new wrap compression system for patients with lower limb ulceration and oedema - Barker, Alison; Todd, Marie (British Journal of Nursing, 2019)
JOBST® FarrowWrap® is indicated in patients presenting with venous leg ulceration in combination with mild-to-moderate oedema. These symptoms result in significant physical and psychological problems and management can be costly in terms of duration of input and resources. This article will present four case studies demonstrating the benefits and outcomes for patients with lower limb issues and will consider how the product helps improve shape, reduce oedema, heal ulceration, improve quality of life in relation to the lower limb and encourage self-care.